2013
DOI: 10.1055/s-0033-1348028
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Mechanically Extracted Breast Milk

Abstract: High concentrations of bacteria are frequently observed in expressed breast milk. The study provides evidence that these bacteria are in the breast milk directly after emission. The pumping procedure and further transportation to the milk bank are of no influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Literature data demonstrate that the contamination with potentially pathogenic bacteria of expressed human milk in NICU can achieve the 40%, however, there are no specific guidelines regarding mother's milk bacteriological testing and acceptable contamination (34). Our results showed that among all samples of raw mature milk, the 15% had positive culture at baseline but this colonization remained stable during the first 72 hours of refrigeration without showing an increase in bacterial load.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data demonstrate that the contamination with potentially pathogenic bacteria of expressed human milk in NICU can achieve the 40%, however, there are no specific guidelines regarding mother's milk bacteriological testing and acceptable contamination (34). Our results showed that among all samples of raw mature milk, the 15% had positive culture at baseline but this colonization remained stable during the first 72 hours of refrigeration without showing an increase in bacterial load.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, microbiological testing of EBM identified bacterial growth in 75% of samples. 16 The relatively high rate of EBM contamination in the present study is attributed to the multiple gaps in the processes of milk expression, storage and transport. It is important to note that in spite of the fact that mothers were instructed about the technical and hygienic aspects of breast milk expression, the compliance rate was not satisfactory.…”
Section: Discussionmentioning
confidence: 67%
“…There are four species isolated: Staphylococcus coagulase, Escherichia coli, Klebsiella pneumoniae and Streptococcus faecalis. Mense et al (2013) observed the bacterial contamination of mecanically extracted breast milk in 50 mother including species of Staphylococcus coagulase, Escherichia coli, Klebsiella pneumoniae and Streptococcus faecalis. The other species were Staphylococcus aureus, Alpha-hemolytic streptococci and dermal bacteria.…”
Section: Discussionmentioning
confidence: 99%